The textual terrain: developments and directions in women's writing, 1500–1700. Issue 170 (November 2022) - Coolahan, Marie-Louise
Abstract: This article assesses our much-expanded view of the texts produced by early modern women in Ireland, surveying what is available to present-day researchers and considering emerging methodologies for the analysis of early modern female voices. The range of genres with which we now know early modern women engaged owes much to feminist literary historians' capacious approach to defining literature, expanding beyond traditionally elite genres (drama, poetry, fiction) to encompass writing in all its forms. Thus, the present corpus includes letters and petitions, life writing, devotional prose, legal depositions, as well as all kinds of verse and song, in multiple languages. Moreover, where the primary evidence in Ireland sometimes seems sparse, international perspectives have illuminated the currents of women's writing. Interpretative paradigms from other fields — book history and the history of reading, culinary and medical history, network analysis — are being applied to yield fresh insights about this material. The question of how early modern Ireland was experienced by women has been explored in studies that address such texts as articulations of subjectivity, in the light of the history of emotions. The wide range of situations and genres of women's writing in early modern Ireland is now firmly evident, inspiring a host of new approaches.